Improving Financial Performance to Social Disclosure of Sharia Bank Performance Based on Islamic Social Reporting Index - Delli Maria; Reva Meiliana (Proceeding International Conference on Information Technology and Business, 2017)
This study aims to examine the role of Social Banking Performance Disclosure to improve the financial performance of sharia banks. This study uses a sample of Sharia Commercial Banks in Indonesia that publishes annual report. Hypothesis testing using simple regression with 95% confidence level. The main variables used in this study consist of six disclosure themes with ISR index, ie funding and investment, products and services, employees, community, environment, and corporate governance. The results of this study indicate the Disclosure of Funding and Investment, Products and Services, Employees and Society has no effect on the Financial Performance of Sharia Commercial Banks in Indonesia. While the disclosure of the Environment and the Manpower Statement of the Company has a significant and significant impact on the Financial Performance of Sharia Commercial Banks in Indonesia.Keywords: Bank Syariah Financial Performance, and Islamic Social Reporting Index.